Atividade antimicrobiana de fenóis naturais contra microrganismos isolados do trato genital de éguas - Lorenzoni, Priscila de Oliveira (2022)
Endometritis is one of the main causes of infertility in mares, generating economic losses in the equine reproduction sector. The difficulty in treating this disease is related to the emergence of resistant strains and the limited range of drugs available